Articular and Peripheral Nervous System Involvement Are Linked to the Long-Term Outcome in Primary Sjögren's Syndrome: The Relevance of Single Organ Manifestations Rather Than a Composite Score as Predictors - Quartuccio, Luca; Gandolfo, Saviana; Zabotti, Alen; Zandonella Callegher, Sara; Fabro, Cinzia; De Vita, Salvatore (Frontiers in Immunology, 2019)
Objective. The disease course in primary Sjögren’s Syndrome (pSS) differs in different subsets of patients. The aim of this study was to clarify whether the pattern of organ involvement may improve the prediction of the very long-term disease outcome. Methods. We collected the data of 255 patients. The total ESSDAI score was compared with the pattern of organ involvement, as differentiated by the single ESSDAI domains: i) at disease diagnosis, and ii) in the follow-up, by verifying the appearance of new ESSDAI domains and/or the worsening of already active ESSDAI domains. Results. The mean follow-up duration was 9.1+6.9 years. At disease diagnosis, only the articular activity at baseline could predict the long-term outcome of pSS detected at last follow-up visit, being protective in terms of stable or improved disease activity, as measured by ESSDAI [OR 2.9 (1.6-5.4), p=0.01]. In the follow-up, the onset and/or worsening of either the peripheral nervous system domain (by multivariate and univariate analysis), or the biological domain (only by univariate analysis) correlated with a higher disease activity at the last visit [PNS domain: OR 5.9 (2.4-14.5), p<0.0001; biological domain: OR 1.9 (1.0-3.8), p=0.043]. A significantly higher number of patients with articular involvement were taking hydroxychloroquine at the last follow-up visits, if compared with patients without (41/130, 31.5% vs 13/125, 10.4%, p<0.0001). Conclusion. Single organ disease manifestations of SS, herein identified as the articular, PNS and biologic involvement, are relevant to to predict the very long-term outcome in pSS.